Assessing research self-efficacy and attitudes among medical students: a quasi-experimental study evaluating the impact of a structured training program - Adebayo Falola; Toluwase Oluwajomiloju Ogundipe; Jonas Paul Ibekwe; Daniel Esanju; Chukwuebuka Asogwa; Balgees Altayib; Ketra Venesa Nandera; Boluwatife David Elusiyan; Chijioke David Mgbeobukwa; Miracle Ifeoluwani Abraham; Jolly Akor Thomas; Afeezah Wojuade; et al. (BMC Medical Education)
Abstract Background Exposure of medical students to research improves their scientific output and future involvement in research. This is particularly important for Africa, where, despite the high disease burden, the continent contributes only 2% of the global research output. An important approach to address this is early introduction of students to research. This study aims to assess the effects of a training organized by the Federation of African Medical Students’ Associations, on self-efficacy and attitudes of medical students to research. Methods A pre- and post-training cross-sectional survey of medical students who participated in the research training was conducted. Ethical approval and informed consent were obtained. Data was collected using pre-tested self-administered questionnaires, and was descriptively analyzed. The Clinical Research Appraisal Inventory-12 scale was used to investigate self-efficacy, and the Attitudes Towards Research scale was used to assess attitudinal changes. Mann–Whitney U test, and Independent Samples t-test were used to compare pre- and post- intervention scores. Results A total of 223 students from eleven African countries who registered for the training were enrolled. However, 152 completed the intervention. Age range was 15–40, with peak age being 21–25. Male to female ratio was 1:1.1. Majority (67%) of the participants were from Nigeria, and in their fourth year (27%). The scores of all six self-efficacy factors increased after the intervention with statistical significance. These included designing and collecting (27.3% to 57.0% p < 0.001); reporting, interpreting, and presenting (28.4% to 60.3% p < 0.001); conceptualizing and collaborating (32.7% to 63.2% p < 0.001); planning (31.8% to 60.7% p < 0.001); funding (21.3% to 53.7% p < 0.001); protecting (33.6% to 65.7% p < 0.001). Positive attitudes towards research increased significantly after the intervention with a mean score of 74.6% to 81.0% (p = 0.001), while negative attitudes decreased (48.9% to 42.9% p = 0.003). Conclusion Structured research training improves the self-efficacy and attitudes of students towards research, and thus should be incorporated into curricula. There is a need for longitudinal studies to further establish the long-term effects of early exposure of medical students to research.